Hidrocarbonetos policíclicos aromáticos no meio ambiente: diferenciação de fontes em sedimentos e metabólitos em bile de peixes - Meniconi, Maria de Fátima Guadalupe (2007)
Many studies on environmental ecosystems quality related to polycyclic aromatic hydrocarbons (PAH) have been carried out routinely due to their ubiquotus presence worldwide and to their potential toxicity after its biotransformation. PAH may be introduced into the environmet by natural and anthropogenic processes from direct runoff and discharges and indirect atmospheric deposition. Sources of naturally occurring PAHs include natural fires, natural oil seepage and recent biological or diagenetic processes. Anthropogenic sources of PAHs, acute or chronic, are combustion of organic matter (petroleum, coal, wood), waste and releases/spills of petroleum and derivatives (river runoff, sewage outfalls, maritime transport, pipelines). Besides the co-existence of multiples sources of PAH in the environmental samples, these compounds are subject to many processes that lead to geochemical fates (physical-chemical transformation, biodegradation and photo-oxidation), which leads to an alteration of their composition. All these facts make the identification of the hydrocarbons sources, if petrogenic, pyrolytic or natural, a challenge. One of the objectives of this study is to establish tools to identify the origin of hydrocarbons in environmental samples. PAH diagnostic ratios and PAH principal component analysis were tested on a critical area: Guanabara Bay sediments. Guanabara Bay is located in a complex urban area of Rio de Janeiro with a high anthropogenic influence, being an endpoint of chronic pollution from the Greater Rio and it was the scenario of an acute event of oil release in January 2000. It were quantified 38 compounds, parental and alkylated PAH, in 21 sediment samples collected in two surveys: 2000 and 2003. The PAH levels varied from 400 to 58439 ng g-1. Both tested techniques for origin identification of hydrocarbons have shown their applicability, being able to discriminate the PAH sources for the majority of the samples analysed. The bay sediments were separated into two big clusters: sediments with a clear pattern of petrogenic introduction of hydrocarbons (from intertidal area) and sediments with combustion characteristics (from subtidal region). Only a minority of the samples could not display a clear contribution of petrogenic or pyrolytic input. The diagnostic ratios that have exhibited high ability to distinguish combustion- and petroleum-derived PAH inputs for Guanabara Bay sediments were Phenanthrene+Anthracene/(Phenanthrene+Anthracene+C1Phenanthrene); Fluorantene/(Fluorantene+Pyrene); Σ (other 3-6 ring PAHs)/ Σ (5 alkylated PAH series). The PCA results prooved to be a useful tool for PAH source identification in the environment, corroborating the diagnostic indexes. In relation to the temporal evaluation carried out in this study, it was not verified significant changes on the class of predominant source of the samples. This result indicates that the hydrocarbons present in the Guanabara Bay sediments are mainly related to the long-term anthropogenic input and not directly related to acute events such as the oil spill of January 2000. This findings were similar to various international estuarine sites. Finally, this work had a complementary objective of evaluating the level of hydrocarbons exposure of the aquatic organisms of Guanabara Bay. It was a preliminary study in which a quantification of 12 individual biliar metabolites of PAH was performed in four demersal fish representing three different families. The analysed metabolites were 1-hydroxynaphtalene, 2-hidroxinaphtalene, 1hydroxyphenanthrene, 9-hydroxyphenanthrene, 2-hydroxyphenanthrene, 1hydroxypyrene, 3-hidroxibiphenil, 3- hydroxyphenanthrene, 1-hydroxychrysene, 9hydroxyfluorene, 4-hydroxyphenanthrene, 3-hydroxybenz(a)pyrene. The metabolites concentrations were found to be high, ranging from 13 to 177 µg g-1, however they were similar to worldwide regions under high anthropogenic input. Besides the metabolites established by the used protocol, it was possible to verified high concentrations of three other compounds not yet reported in the literature. They were related to pyrolytic PAH contribution to Guanabara Bay aquatic biota: 1-hydroxypyrine and 3-hydroxybenz(a)pyrine isomers